Innovation Capability, Knowledge Management and Big Data Technology: A Maritime Business Case - Lambrou, Maria (International Journal of Advanced Corporate Learning (iJAC), 2016)
We present an updated knowledge management approach to foster companies’ proficiency to formulate and implement their innovation strategies for new business models, services and markets, interlinked with knowledge management and learning technology resources and capabilities, in today’s highly uncertain environment. We elaborate the generic framework, also in view of a maritime business case.